The Resilience of Coffee Roastery in the Downtown Area; Case Study of The Coffee Lab Dubai - Kurniawan Arif Maspul (PROGRAM STUDI ILMU KOMUNIKASI, 2021)
The vast number of coffee roasteries opened in Dubai is a unique highlight of how regulations serve, following how sustainability impacts society. The author performed this case study based on data pertained as a coffee roaster at The Coffee Lab Dubai. Delineated qualitatively and revealed the retail resilience of The Coffee Lab as one of the most sustainable businesses in the UAE. In this case study, the author used to collect the data from the work area at The Coffee Lab, such as coffee production and all things related to the business establishment since its opening until March 23, 2020. Since the first day of work, the author collected the data and recorded manually through the Microsoft Excel for the actual numbers in daily closing, especially in coffeeshop's consumption. The author is the certified Person in Charge (PIC) of The Coffee Lab and Authorized Specialty Coffee Association Trainer (AST) for roasting. The Coffee Lab used to do more production in roasting and has been continuously supplied an enormous number of coffee shops in the UAE and the GCC countries. By March 2020, the show reached an average of 1.2 tons/month. Using the Loring F15, saving the emission of gas more than the usual coffee roaster machine, the capacity of 15kg was quite good enough for daily production from 70 -200kg. Meanwhile, the most important of the coffee roastery as well as the plan of Hazard Analysis Critical Control Path (HACCP), which should be well-approved by the Dubai Municipality Coffee production, specifically roasting, has long fallen under the radar when it comes to food safety concerns at manufacturing facilities, and for the coffee roasters who operated them. Anyone who helped set up or maintain written food safety plans for a roasting operation knows that one of the critical elements is a Hazard Analysis Critical Control Path (HACCP) plan.